2015
DOI: 10.5772/60114
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Routines in Engineering Managers and Non-Engineering Managers — A Case Analysis

Abstract: There is a perception that engineers experience challenges in areas such as communication, conflict resolution, and leadership. Defensive routines are actions implemented as a result of being in an embarrassing or threatening situation. This research uses a case study approach to measure whether defensive routines are more common in engineering managers or non-engineering managers. Twenty-seven managers created case studies based on their unique experiences as managers. These case studies were scored, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This is in broad agreement with the conclusions of authors such as [3], who asserts that knowledge barriers as avoiding embarrassment hinders the process of sharing knowledge, which in turn can hinder the possibility of using alternative technologies [51]. It is a pity but the act of asking is often associated with something negative or embarrassing, because people in general and knowledge workers in particular tend to believe that they will be perceived as less intelligent, distracted, or simply incompetent [14], [52], [93]. In other words, the more embarrassed one feels about asking technology issues or environmental issues, the less learning takes place.…”
Section: A Implications For Theorysupporting
confidence: 88%
See 1 more Smart Citation
“…This is in broad agreement with the conclusions of authors such as [3], who asserts that knowledge barriers as avoiding embarrassment hinders the process of sharing knowledge, which in turn can hinder the possibility of using alternative technologies [51]. It is a pity but the act of asking is often associated with something negative or embarrassing, because people in general and knowledge workers in particular tend to believe that they will be perceived as less intelligent, distracted, or simply incompetent [14], [52], [93]. In other words, the more embarrassed one feels about asking technology issues or environmental issues, the less learning takes place.…”
Section: A Implications For Theorysupporting
confidence: 88%
“…Previous studies have highlighted the importance of having the necessary knowledge to respond to customer demands and thus be able to improve the reputation of the company [11]- [13]. However, in order to learn and generate that knowledge, it is necessary to overcome the fear of making a fool, not liking or saying something inappropriate [4], [14]. Few if any studies so far have been able to precisely state the role played by green skills and technology assimilation as a way to overcome embarrassment in addressing technology issues and improve the company's reputation.…”
mentioning
confidence: 99%
“…Individuals in organizations mindlessly follow these governing principles and automatically adopt skills to avoid embarrassment and threat. As a result, individuals’ defensive routines become prevalent resulting in organizational level ODRs (Riley and Cudney, 2015). Therefore, Argyris (1996) argues that individual defensiveness is the origin of ODRs, but simultaneously ODRs operate like a fertilizer, by nurturing individual defensiveness and making it more acceptable in organizations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While these two problem statements are underpinned by different philosophical paradigms, authors whose work we have grouped together in this section advocate for a similar solution-help engineers develop the necessary skills, traits and styles to be effective leaders or managers. Two authors argued that managers of engineers should be responsive to the particular needs, personality types and learning styles of engineers [10,11], two compared the leadership styles of engineering managers to non-engineering managers [12,13], seven urged engineering leaders to develop their social, interpersonal and communication skills [14][15][16][17][18][19][20], and the remaining two warned us against characterizing engineers' leadership styles in a culturally neutral manner [21,22].…”
Section: Literature Review: Engineers' Leadership Learningmentioning
confidence: 99%
“…In contrast to Mallette and Wyrick who wrote to an audience of managers hoping to effectively direct the work of engineers, Riley [13], Brown [12] and their respective colleagues studied the styles and personality attributes of engineers who were themselves leaders. Riley and Cudney conducted a small-scale, mixed-methods study on the leadership styles of engineering managers and non-engineering managers across technical industries in the United States and found that engineers were more likely than non-engineers to engage in defensive behaviours when encountering conflict.…”
Section: Literature Review: Engineers' Leadership Learningmentioning
confidence: 99%